Mate [large type] - Hazelwood, Ali (Thorndike Press, 2025)
"Serena Paris is orphaned, pack-less, and one of a kind. Coming forward as the first Human-Were hybrid made her a target, prey to the ruthless political machinations between Weres, Vampyres, and Humans. With her enemies closing in on her, she has only one option left - if he'll have her. As Alpha of the Northwest pack, Koen Alexander commands obedience. It doesn't matter if Serena doesn't reciprocate his feelings, nothing will stop him from keeping her safe. But power-hungry Vampyres and Weres are not the only threats chasing Serena. Sooner or later, her past is bound to catch up with her - and Koen might be the only thing standing between her and total annihilation."